2022
DOI: 10.3390/molecules27020420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxyl Groups Esterification with Fatty Acids on the Cytotoxicity and Antioxidant Activity of Flavones

Abstract: Flavonoids and polyunsaturated fatty acids due to low cytotoxicity in vitro studies are suggested as potential substances in the prevention of diseases associated with oxidative stress. We examined novel 6-hydroxy-flavanone and 7-hydroxy-flavone conjugates with selected fatty acids (FA) of different length and saturation and examined their cytotoxic and antioxidant potential. Our findings indicate that the conjugation with FA affects the biological activity of both the original flavonoids. The conjugation of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…However, other flavonoid/fatty acid derivatives were investigated. As regards the more elevated cytotoxic potential of RUT-O compared to RUT-L, a similar observation has been made by Kubiak-Tomaszewska et al whose study revealed that oleic derivatives of 6-hydroxy-flavanone and 7-hydroxy-flavanone (0-100 µM) had an increased cytotoxic effect both in HaCaT keratinocytes and PC3 prostate cancer cells following a 72 h treatment compared to the linoleic conjugates and to the parent compounds (Kubiak-Tomaszewska et al, 2022). In other study, OA and LA esters of quercetin-3-O-glucoside were shown to possess no cytotoxicity to human primary hepatocytes, while exerting a cytoprotective effect by overcoming the H 2 O 2 -induced damage (Warnakulasuriya and Ziaullah, 2016).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, other flavonoid/fatty acid derivatives were investigated. As regards the more elevated cytotoxic potential of RUT-O compared to RUT-L, a similar observation has been made by Kubiak-Tomaszewska et al whose study revealed that oleic derivatives of 6-hydroxy-flavanone and 7-hydroxy-flavanone (0-100 µM) had an increased cytotoxic effect both in HaCaT keratinocytes and PC3 prostate cancer cells following a 72 h treatment compared to the linoleic conjugates and to the parent compounds (Kubiak-Tomaszewska et al, 2022). In other study, OA and LA esters of quercetin-3-O-glucoside were shown to possess no cytotoxicity to human primary hepatocytes, while exerting a cytoprotective effect by overcoming the H 2 O 2 -induced damage (Warnakulasuriya and Ziaullah, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…By comparing the tested REs, the computational predictions indicated a higher lipophilicity (cLogP) and lower solubility for RUT-O than for RUT-L. Correlated to the viability and Hoechst 33342 results, it can be assumed that the increased hydrophobic degree results in enhanced cell membrane crossing and thus a slightly elevated toxicity of the OA-derivative towards healthy H9c2(2-1), HepaRG, and HaCaT cells in comparison to the LA-conjugate, highlighted via reduced cell viability and nuclear dysmorphology. Similar conclusions were expressed by other researchers observing a possible link between the lipophilic properties of flavonoid conjugates, their cellular uptake, and consequent cytotoxicity (Danihelová et al, 2013;Kubiak-Tomaszewska et al, 2022). Viskupicova et al showed that the lipophilic derivatization of rutin using fatty acids (such as OA and LA, among others) effectively increases its hydrophobicity and solubility in fats (Viskupicova, 2010).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The hydroxyl radical scavenging activity was assayed according to references [ 44 , 45 ]. The EAE and CE of RG and SGD were dissolved in 20% DMSO, and the other extracts were dissolved in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that hydroxyl groups at specific positions on the aromatic ring can increase antioxidant activity. [76][77][78][79][80] Thus, the position of the hydroxyl group greatly influences the ability of a compound to scavenge free radicals. Research has explained that the removal of hydroxyl groups decreases the ability of compounds to scavenge free radicals.…”
Section: Isolation and Identification Of Secondary Metabolitesmentioning
confidence: 99%